Amoeboma in a Saudi resident: a case report. Issue 3 (10th June 2016) - Al Rehily, Sanaa; Kaki, Reham; Al Ghamdi, Fahad; El-Hossary, Dalia
Abstract : Introduction: Amoebiasis is the third most frequent cause of mortality after malaria and schistosomiasis. In developed countries, amebiasis is also seen in migrants who have travelled to endemic areas. The factors responsible for its progression from intestinal amebiasis to an amebic liver abscess are not fully understood. Case presentation: A 54-year-old man presented with abdominal pain, fever and diarrhoea. Laparotomy confirmed an inflammatory mass involving the right colon, and he underwent a right hemicolectomy. He later developed abdominal distenstion due to an amoebic liver abscess and died from secondary nosocomial bacterial infection and surgical complications. Conclusion: Amoeboma is an uncommon manifestation of amoebiasis, and can mimic both carcinoma and inflammatory bowel disease; so, distinguishing between these two conditions is the key to providing appropriate therapy. Hepatic amoebiasis is the most common extraintestinal disease of invasive amoebiasis. This clinical report presents a case of an uncommon parasitic disease in Saudi Arabia and discusses the difficulties encountered while attempting to establish the correct diagnosis. Hence, a high index of suspicion is crucial for diagnosing Entamoeba histolytica to avoid unnecessary surgery and further complications.